Assessment of the possibility of replacing solid rivets in joints of aircraft structure - Rośkowicz, Marek; Tkaczuk, Sławomir; Komorek, Andrzej; Gąsior, Jarosław (Technologia i Automatyzacja Montażu (Assembly Techniques and Technologies), 2018)
The paper presents the results of experimental research, the aim of which was to assess the possibility of replacing rivets with solid one-sided rivets in connections of aircraft structures. Because one-sided rivets, in contrast to solid rivets, consist of many elements, the evaluation as a comparative criterion assumes not only the load capacity of connections, but also the resistance to the phenomenon of automatic dismantling of one-sided rivets subjected to a variable load. In fatigue tests, it was found that there is a possibility of replacing rivets with solid one-sided rivets, but the fatigue life of joints of one-sided joint connections depends significantly on the place of rupture of the one-sided blind pin in its heading process. This is an Open Access article distributed under the terms of the Creative Commons Attribution License CC BY 4.0 (https://creativecommons.org/licenses/by/4.0/)